Pro-inflammatory effects of DEHP in SGBS-derived adipocytes and THP-1 macrophages - Kristina Schaedlich (Nature Portfolio, 2021)
Abstract In the member countries of the Organization for Economic Co-operation and Development (OECD), overweight and obesity affect the majority of the population. The use of environmental chemicals, such as the plasticizer DEHP, has largely increased simultaneously with this development. DEHP is an "obesogen" that interferes with normal adipocyte differentiation and energy homeostasis. Obesity in turn is accompanied by chronic low-grade adipose tissue inflammation, leading to metabolic disorders such as type II diabetes. The main actors in adipose tissue inflammation are adipocytes and macrophages. However, the impact of DEHP on adipose tissue inflammation and the crosstalk between adipocytes and macrophages are unknown and the subjects of the current study. The influence of DEHP on inflammation was investigated in human Simpson–Golabi–Behmel syndrome (SGBS)-derived adipocytes and human THP-1 macrophages. The proinflammatory markers IL8, MCP1, IL1β, TNFα and others were measured (qRT-PCR, ELISA) in SGBS-derived adipocytes treated with DEHP [day 0 (d0)–d4; 50 µg/ml] and THP-1 macrophages cultured with conditioned medium (CM) from DEHP-treated adipocytes (SGBS-CM) (from d4 and d8). DEHP exposure led to a proinflammatory state in SGBS-derived adipocytes (e.g., increased secretion of IL8 and MCP1). Surprisingly, exposure of THP-1 macrophages to SGBS-CM did not show DEHP-induced effects. However, we demonstrated that medium containing (pre)adipocyte-secreted factors had a significant impact on the expression and secretion of macrophage and inflammatory markers in THP-1 macrophages in general and led to the significantly increased accumulation of intracellular lipid droplets.